Characterization of an eye prosthesis using monopoly syrup - Pinki Bankoti; M K Singhal; Chandana Nair; Praveen Chandra (Wolters Kluwer Medknow Publications, 2016)
The eye is a vital organ and an important component of facial expression. Loss of an eye has a crippling effect on the psychology of the patient. Maxillofacial prostheses restore and replace stomatognathic and associated facial structures with artificial substitutes. The objectives of eye prosthesis is to improve the patient esthetics, restore and maintain the health of the remaining associated structures, consequently provide physical and mental well-being. The primary purpose of an ocular prosthesis is to maintain the volume of eye socket and create the illusion of a healthy eye and surrounding tissue. A custom ocular prosthesis is a good option when reconstruction is done by plastic surgery, and osseointegrated implants are either not possible or not desired. A case of a custom-made ocular acrylic prosthesis is presented with acceptable fit, good retention, and esthetics.